The Competitiveness Of The Pharmaceutical Industry In Malaysia: An Application Of Extended Porter’S Diamond Model - Chong, Hooi Ying (2022)
The Malaysian pharmaceutical manufacturing industry is facing several competitiveness issues. Among the issues are declining profitability, an increase in the number of competitors, poor export performance, limited production capacity, and a lack of innovation capabilities. Previous pharmaceutical competitiveness literature demonstrates that home country business environment factors play an important role in determining the industry competitiveness in international trade. However, the relationship between home country business environment factors and pharmaceutical firm competitiveness in terms of profitability and market share remains largely unexplored. Therefore, the purpose of this study is to investigate the influences of national business environment factors on pharmaceutical firm competitiveness for a sample of 30 prescription medicines manufacturing firms operating in Malaysia from 2004 to 2018. The theoretical foundation for this research is primarily derived from Porter's Diamond Model. Static panel regression method is used to estimate the relationships between home country business environment factors and the firm competitiveness of the Malaysian pharmaceutical manufacturing industry.